A new species of Agistemus (Acari: Stigmaeidae) as a predatory agent of eriophyid mites in olive orchards in Guilan, Iran - Mohammad Khanjani; Jalil Hajizadeh; Hamed Zarei Dogh-abadi; Mohammad Ahmad Hoseini (Persian Journal of Acarology)
A new species, Agistemus manjilicus Khanjani, Hajizadeh & Zarei sp. nov. was collected from olive leaves and litter in olive orchards, Olea europaea L. (Oleaceae) in Manjil vicinity, Guilan province, Iran, is described and illustrated.